Diagnostic accuracy of OGUS, Southend halo score and halo count in giant cell arteritis - Conticini, Edoardo; Falsetti, Paolo; Al Khayyat, Suhel Gabriele; Grazzini, Silvia; Baldi, Caterina; Bellisai, Francesca; Gentileschi, Stefano; Bardelli, Marco; Fabiani, Claudia; Cantarini, Luca; Dasgupta, Bhaskar; Frediani, Bruno (Frontiers in Medicine, 2024)
Objectives Ultrasound has a paramount role in the diagnostic assessment of giant cell arteritis (GCA); Southend halo score (HS), halo count (HC), and OMERACT GCA Ultrasonography Score (OGUS) are the first quantitative scores proposed in this setting. The aim of this study was therefore to assess the diagnostic accuracy of these scores in a real-life scenario, as well as to evaluate their optimal cutoff, also with respect to disease extent, sex, and age. Methods We retrospectively collected clinical, serological, and US findings of all patients referred for the first time to our vasculitis clinic in the suspicion of GCA. Results A total of 79 patients were included, and a definite diagnosis of GCA was made in 43 patients. For OGUS, the ROC curve showed an optimal cut point of 0.81 (sensitivity 79.07% and specificity 97.22%). For HC and HS, the optimal cutoff values were > 1.5 (sensitivity 76.7% and specificity 97.2%) and > 14.5 (sensitivity 74.4% and specificity 97.2%), respectively. No relevant differences were assessed when patients were stratified according to disease extent, age, and sex. Compression sign (CS) was positive in 34 of 38 patients with cranial GCA and negative in all controls and LV-GCA. Conclusion All three scores display good sensitivity and excellent specificity, although the cutoff was slightly different than proposed. In particular, for OGUS, a threshold of 0.81 could be employed for diagnostic purposes, although it was developed solely for monitoring. Due to its high sensitivity and specificity, CS should be always assessed in all patients referred with a suspicion of cranial GCA.